Acrylic Bone Cements Modified with Graphene Oxide: Mechanical, Physical, and Antibacterial Properties (2020)
Bacterial infections are a common complication after total joint replacements (TJRs), the treatment of which is usually based on the application of antibiotic-loaded cements; however, owing to the increase in antibiotic-resistant microorganisms, the possibility of studying new antibacterial agents in acrylic bone cements (ABCs) is open. In this study, the antibacterial effect of formulations of ABCs loaded with graphene oxide (GO) between 0 and 0.5 wt.% was evaluated against Gram-positive bacteria: Bacillus cereus and Staphylococcus aureus, and Gram-negative ones: Salmonella enterica and Escherichia coli. It was found that the effect of GO was dependent on the concentration and type of bacteria: GO loadings ≥0.2 wt.% presented total inhibition of Gram-negative bacteria, while GO loadings ≥0.3 wt.% was necessary to achieve the same effect with Gram-positives bacteria. Additionally, the evaluation of some physical and mechanical properties showed that the presence of GO in cement formulations increased wettability by 17%, reduced maximum temperature during polymerization by 19%, increased setting time by 40%, and increased compressive and flexural mechanical properties by up to 17%, all of which are desirable behaviors in ABCs. The formulation of ABC loading with 0.3 wt.% GO showed great potential for use as a bone cement with antibacterial properties.